Spatiotemporal correlations between traps, carbonatites and kimberlites - Aryasova, O. V.; Khazan, Ya. M. (Geofizicheskiy Zhurnal, 2012)
Based upon the most complete modern plateau basalt, carbonatite and kimberlite databases, we show the existence of spatiotemporal correlations between these three types of intraplate magmatism. These correlations are evident everywhere in Eurasia and Africa but they are absent in North America. A probable cause of such correlations is an interaction of a giant plume «head» with the lithosphere, which generates almost simultaneous magmatic activity over a territory of a few thousand kilometers across with magma volume and composition depending on the tectonic structure and thermal state of lithosphere. A distinction of Eurasia and Africa on one side and North America on the other is probably related to the fact that during the last 350 M years North America in contrast to Eurasia and Africa were not situated above the African and Pacific zones of plume generation.